Kepemilikan Tanah Oleh Warga Negara Asing Melalui Perjanjian Pinjam Nama Sebagai Bentuk Penyelundupan Hukum Dalam Hukum Perdata Internasional - Yosia Hetharie (Fakultas Hukum Universitas Pattimura, 2022)
Introduction: Land as a gift from God Almighty deserves to be protected, managed and preserved. In the regulation of land law in Indonesia, based on the UUPA, land ownership with property rights is only by Indonesian citizens. The practice that occurs is that foreigners who carry out legal smuggling efforts through name-borrowing agreements to be able to control and own land in Indonesia with property rights.Purposes of the Research: This study aims to analyze the practice of borrowing names in land ownership by foreigners in Indonesia as a form of international civil law smuggling.Methods of the Research: This study uses a normative juridical method. The approach used is a statutory approach and a conceptual approach with primary and secondary legal sources. The technique of collecting legal materials is through literature study. The legal materials obtained were analyzed qualitatively in order to answer the existing problems.Results of the Research: A name borrowing agreement is an agreement made between a person who according to law cannot be the subject of certain land rights (property rights), in this case a foreigner and an Indonesian citizen, with the intention that the foreigner can control (own) the right of ownership legally. facto, but legally-formally (dejure) the property rights are in the name of the Indonesian citizen. The name-borrowing agreement is clearly a form of legal smuggling to avoid regulations that stipulate that foreigners are not eligible as subjects of land ownership rights holders in Indonesia in accordance with the provisions in Article 9 paragraph (1) jo. Article 21 paragraph (1) of the UUPA clearly states that only Indonesian citizens can have full relations with the earth, water and space, and clearly stipulates that only Indonesian citizens can have property rights.